Pyrotechnic Films Based on Thermites Covered with PVC. Issue 1 (25th November 2018) - Smit, Kenneth J.; Morgan, Michael; Pietrobon, Raoul
Abstract: Incorporation of pyrotechnics into a polymer film of approximately 0.5 mm thick can be used to conveniently prepare pyrotechnics for characterization and demonstration purposes as shown with various thermites. Pyrotechnics may be prepared from fuels and oxidants as sieve mixed powders or dispersed into liquids and mixed together. In this way thermites, including nanothermites, may be prepared as solid films. The matrix of the film is composed of poly(vinyl chloride) however the thermite still undergoes solid thermite reactions because the majority of the polymer dries above the pyrotechnic layer. The process also facilitates control over thermite ignition as shown when appropriate priming layers are sequentially added to ignite an Al/Fe2 O3 thermite layer. The resultant product of the additive manufacturing technique is a multilayered pyrotechnic thin film. Abstract :